Shorea genus / Nur Balqis Farhanis Idris - Idris, Nur Balqis Farhanis (2009)
Meranti is the species that are mostly found in Southeast Asia. It becomes an asset to the Southeast Asia countries. Furthermore, The family of Meranti is very big and it has been divided into six groups which are Dark Red Meranti, Light Red Meranti, White Meranti , Yellow Meranti , Balau and Melantai. The Meranti trees can be determined by the observation from the characteristics of Meranti trees such as leaf margin, seeds, fruits and habitats. Nowadays, Meranti has been the most popular choice for furniture entrepreneurs. However, Meranti trees are easily infected by the brittle heart disease.